Effect of Maja (Aegle marmelous) Leaf Extract and Trigona Honey on Glucosidase Activity Inhibition - Purnamasari, Ulfa Purnamasari; Marliyati, Sri Anna; Damayanthi, Evy (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2022)
This study aims to determine the effect of the maja leaf extract and trigona honey on the á-glucosidase enzyme inhibition, antioxidant activity, and phytochemical type of trigona honey. It is a completely randomized study with natural ingredients, which are traditionally used for diabetic treatment in South Sulawesi. These Maja leaf extracts were mixed with raw trigona honey under several proportions: F1 (only containing trigona honey), FII (trigona honey mixed with maja leaves extract in ratio of 1:1), FIII (only containing maja leaves extract), FIV (trigona honey and maja leaves extract in ratio of 2:1) and FV (trigona honey and maja leaves extract in ratio of 1:2). The five formulas were tested for the phytochemical content (flavonoid, alkaloid, tannin, triterpenoid, steroid, saponin, and quinones), antioxidant activity by DPPH method and followed by á-glucosidase enzyme inhibition test. The phytochemical test found that trigona honey only contained flavonoid and tannin compounds, whereas maja leaf extract and its mixture (with trigona honey) obtained a positive result of flavonoid, tannin, steroid, and saponin contents. Meanwhile, the antioxidant activity results are categorized as follows (IC50): FI (2,524 ppm) has a very weak antioxidant activity, FII (196 ppm) has a weak antioxidant activity, FIII (201 ppm) and FIV (225 ppm) have very weak antioxidant activities, FV (147 ppm) has a moderate antioxidant activity. The results of the á-glucosidase inhibition test show that the highest value was in FV (300.74 ppm), then followed by FIII (493.54 ppm), and FIV (847.95 ppm). On the other hand, FI and FII formulas were considered unable to inhibit á-glucosidase enzymes. Therefore, adding Maja leaf extract into the trigone honey might improve its potential use for managing diabetes